Effects of 7 SNPs on growth and meat quality traits in F1crossbred of Korean native pig × Duroc - KIM, J W; LEE, J Y; SINGH, N K; CHOI, S Y; KIM, H; PARK, S R; LEE, Y S; JEONG, D K; LEE, J K; LEE, S K; LEE, S J (The Indian Journal of Animal Sciences, 2015)
The study was designed to investigate genetic associations of single nucleotide polymorphism (7 SNPs located on 7 selected candidate genes) with growth and meat quality of F1 Korean native pig × Duroc. Selected SNP sets (7) of 86 F1 crossbred pig samples were genotyped by PCR-RFLP. The association analysis revealed that SNPs on MC4R, PGK2 and CTSD genes were significantly associated with body weight. Average daily gain at 2 weeks (ADG2) showed significant associations with SNPs on MC4R and PGK2. On the other hand, ADG10 showed associations only with SNP on MC4R. In addition, backfat thickness and pH value also exhibited significant associations with the SNPs on MC4R, TNNI1, CTSK, CTSZ, and PGK2 genes. Therefore, we concluded that a significant association exists between economic traits and SNPs located on 7 genes. However, further studies seem mandatory to establish the possibility that SNP markers tested here could be used as potential genetic markers for the crossbred Korean native pigs.